Medical students' perspectives on the English B Higher Level program offered by The International Baccalaureate Curriculum in Kolej Mara Banting / Noraini Ahmad Shukri @ Nooruddin - Ahmad Shukri @ Nooruddin, Noraini (2012)
This study investigated which language component in the newly-introduced English B Higher Level subject by International Baccalaureate Diploma in Kolej MARA Banting are most preferred by its pre-medical students. The researcher also investigated and explored the students’ perceptions as to which of these determined components' (Writing, Oral Competency or Literature) they believed have contributed the most to their English proficiency. This particular research is concerned with understanding the participants’ opinions and viewpoints in order to identify and understand the significance of the phenomenon specifically from the participants’ perspectives and this done by distributing a short questionnaire to 68 randomly-selected students and 10 instructors, as well as die study of existing documents, to ensure the data collected through the questionnaires were consistent. This particular study on KMB students’ perception is deemed significant as many of these students felt they are particularly weak in the subject. Initial findings indicated that although, not at the same level of preference, it is safe to conclude that all the aforementioned components are viewed as important not only in contributing to their language proficiency, but also to the outcome of their forthcoming IB examinations. It is also discovered that the greatest students’ preference is for the study of the Literature course. However, it is also observed that the Writing course is considered the most important as respondents see it as relating directly to their performance in the written examinations. The study also indicates that there is a sense of ambiguity and uncertainty in some of the respondents’ responses, which imply towards their lack of aptitude in assessing their own language learning needs and weaknesses in relation to the English B HL program. However, a more significant concern was disclosed by the researcher, a new issue emerged in relation to the concerns regarding the significant disparity of instructors’ individual interpretation and implementation of the prescribed syllabus. The implications of these findings points to the issue concerning the disparity of classroom instructions amongst the language instructors and questions instructors’ own abilities in executing the appropriate language teaching methodology in carrying out the intended syllabus.